2016
DOI: 10.4103/0366-6999.177970
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Urodynamic Analysis of Urinary Dysfunction in Multiple Sclerosis

Abstract: Background:Both lower urinary tract dysfunction and urinary symptoms are prevalent in patients with multiple sclerosis (MS). Although the significance of identifying and treating urinary symptoms in MS is currently well-known, there is no information about the real prevalence and therapeutic effect of urinary symptoms in patients with MS. The purpose of this study was to analyze the major symptoms and urodynamic abnormalities, and observe the therapeutic effect in different MS characteristics.Methods:We enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
5
11
0
1
Order By: Relevance
“…MS with focal demyelinating lesions at different levels of the central nervous system (CNS) leads to urinary dysfunction. [29] In the present study 41.3% of patients had moderate to severe urinary symptoms. This finding was similar to the findings of the study by Sammarco with 43% moderate to severe bladder dysfunction among patients with MS. [14] The high prevalence of LUTS suggests the complexity of neural control of the function of the bladder and urinary tract in health and the location and nature of the neural lesions determines the pattern of bladder dysfunction.…”
Section: Discussionsupporting
confidence: 46%
“…MS with focal demyelinating lesions at different levels of the central nervous system (CNS) leads to urinary dysfunction. [29] In the present study 41.3% of patients had moderate to severe urinary symptoms. This finding was similar to the findings of the study by Sammarco with 43% moderate to severe bladder dysfunction among patients with MS. [14] The high prevalence of LUTS suggests the complexity of neural control of the function of the bladder and urinary tract in health and the location and nature of the neural lesions determines the pattern of bladder dysfunction.…”
Section: Discussionsupporting
confidence: 46%
“…MS with focal demyelinating lesions at different levels of the central nervous system (CNS) leads to urinary dysfunction. [23] In the present study, the prevalence of LUTS was high among patients with MS (reaching to more than ¾ of the patients), and 41.3% of patients had moderate to severe urinary symptoms. This finding was similar to the findings of the study by Nakipoglu with an 80.81% prevalence of LUTS and the study by Sammarco with 43% moderate to severe bladder dysfunction among patients with MS. [13,24] The different estimates reported for the prevalence of LUTS in MS range between 32% and 97%, [25,26] and the high prevalence of LUTS suggests the complexity of neural control of the function of the bladder and urinary tract and the location and nature of the neural lesions determines the pattern of bladder dysfunction.…”
Section: Discussionsupporting
confidence: 45%
“…De Almedia reported prevalence rates of 63.5% and 100%, respectively, among patients with RRMS and primary progressive MS. [43] Moreover, a study by Wang et al showed the lowest OBASS score in patients with CIS. [23] In the present study, patients with MS and LUTS symptoms compared to LUTS-free patients had lower QOL scores in all dimensions except for health changes and there was a significant difference in the combined physical and mental health dimensions of QOL between the two groups with and without LUTS. In addition, there was a higher possibility of a urinary tract complication in patients with MS with a higher EDSS score.…”
Section: Discussionsupporting
confidence: 43%
“…Moreover, such an understanding provides a significant insight into the complicated MS pathophysiology and the mechanism of LUTS in the emergence of MS. These determinants contribute to the management of LUTS and improvement of quality of life (QOL) [15]. Performing epidemiological studies to evaluate the rate of specific symptoms among individuals with MS helps to describe the economic and social significance of the disease and assists in the identification, early diagnosis, and timely control of the complications of the disease [16], and identification of possible causes of the disorder, in addition to providing the foundation for higher level studies [17,18].…”
Section: Introductionmentioning
confidence: 99%